Analisis Tanggung Jawab Belajar Siswa dalam Model Pembelajaran E-Learning di Kelas III SDN Mekarsari I Kabupaten Tangerang - Septiananda, Sabrina; Chudari, Ima Ni'mah (Universitas Pendidikan Indonesia Kampus Serang, 2021)
Elementary School which conducts basic education is an educational institution that organizes educational programs as a basis for student preparation that can be used for higher. Responsibility on learning somehow become important for students in an online learning situation for elementary school students. This research was conducted to analyze the learning responsibility of students in the Mekarsari I public elementary school, Tangerang district. This research uses a qualitative approach with a case study method. The subjects of this study were teachers and students. Through research instruments in the form of observation sheets, interview sheets, and student questionnaires, researchers conducted research in class III with a total of 36 students. The results showed that learning responsibilities such as doing assignments on time and being responsible for the rules that apply in the school of students in the e-learning model in class III Mekarsari I public elementary school was good enough. Because every time students did learning they were responsible according to what was done and according to their abilities with the help of the role of teacher and parents and the role of students learning public elementary school although not optimal or not always perfect.